Monitoring of Public Procurement (SIGMA Public Procurement Briefs, 2013)
Public procurement contracts represent a major share of any country's GDP and public expenditure budget. For this reason monitoring the compliance and performance of public procurement systems is of the utmost importance. For the purposes of SIGMA Brief 27, monitoring of public procurement comprises each and any systematic observation of the public procurement system conducted in a coherent way in order to assess how the system functions and develops over time, and to establish whether the desired state defined by policy makers has been achieved. The Brief gives an overview of EU requirements concerning monitoring, the purpose and role of monitoring as well as types of monitoring. Finally, the Brief gives examples of monitoring in European Union member states